1995
DOI: 10.1007/s002340050177
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of lumbar epidural lipomatosis in obese patients after weight-reduction diet

Abstract: We present three obese patients with symptomatic lumbar epidural lipomatosis. All three were treated with a calorie-controlled diet and considerable weight reduction was achieved. MRI demonstrated a reduction in the epidural fat and relief of thecal sac compression in all three; two also improved clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…SEL is a condition wherein excess adipose tissue deposits around the thecal sac causing compression of neural structures 2,3,5,7,8,12,17,18,24,31,32) . In 1975, Lee et al 18) reported the first case of symptomatic epidural cord compression secondary to SEL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SEL is a condition wherein excess adipose tissue deposits around the thecal sac causing compression of neural structures 2,3,5,7,8,12,17,18,24,31,32) . In 1975, Lee et al 18) reported the first case of symptomatic epidural cord compression secondary to SEL.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of SEL is a matter of debate, because many patients have been treated by simple weight reduction with good results 7,22,24) . However, this conservative treatment remains restricted to patients with mild neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Known predisposing factors are glucocorticoid therapy and Cushing's syndrome [5,6,14], while the idiopathic form has mostly been described in obese patients [6]. Our patient suffered from hyperlipidemia, but he neither showed abnormal fatty distribution at physical examination, nor he had impaired glucose tolerance, which has been reported together as predisposing factors in one patient with symptomatic epidural lipomatosis [15].…”
Section: Discussionmentioning
confidence: 52%
“…Spinal epidural lipomatosis (SEL) is characterized by an excessive deposit of fatty tissue in the epidural space [4]. Obesity and glucocorticoid use are known risk factors for SEL [5,6]. Herein, we describe the MR and pathological findings of a patient presenting with rapidly progressing paraplegia, which MR revealed to be due to spinal cord compression caused by a Staphylococcus aureus abscess in an epidural lipomatosis.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 a, b Myelography showing a dural sac compression particularly at the L5-S1 level Clinical improvement is reported after weight loss, but the reduction in epidural lipomatosis on nuclear magnetic resonance is reported in only a few cases [1,2]. Follow-up CT scan in our patient showed reduction in the accumulation of epidural adipose tissue around L4-L5 and L5-S1 after a weight loss of 17.5 kg, associated with disappearance of low back pain and improved walking distance.…”
Section: Discussionmentioning
confidence: 99%